Linearity response measurement of a SiPM-based dual-readout calorimeter for future leptonic colliders - Antonello, Maddalena; Caccia, M.; Ferrari, R.; Franchino, Silvia; Gaudio, G.; Hauptman, J.; Lee, S.; Pezzotti, L.; Salvatore, F.; Santoro, R.; Vivarelli, I.; Wigmans, R. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
A dual-readout fibre sampling calorimeter module, based on Silicon Photomultiplier readout, was developed and tested on beam in 2016 and 2017. This test completed the proof-of-concept but also revealed a non-linear response to the scintillation light. In 2018, the signal linearity was studied after the interposition of a yellow filter between the scintillating fibres and the sensors. This paper reports the latest results on the module performance, highlighting as well the key and potentially critical parameters and the adopted solutions.
Available online 27 April 2019
Gesehen am 06.04.2020